2022
DOI: 10.3390/antiox11071393
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Genotoxic, Antigenotoxic and Antioxidant Profile of Different Extracts from Equisetum arvense L.

Abstract: The present study investigated the cyto-genotoxic and antigenotoxic effects of four different extracts of Equisetum arvense L. (common name: field horsetail) on human lymphocytes. Specifically, Soxhlet’s prepared extracts from E. arvense L., using different solvents (S1: methanol (MeOH)-, S2: ethanol (EtOH)-, S3: water-, and S4: ethanol/water (EtOH-W)-) were analyzed for (a) their total phenolic and flavonoid content (TPC and TFC, respectively), (b) their antioxidant activity (AA), via the DPPH, FRAP and ABTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…They have well-expressed pharmacological and antioxidant activities [50,[58][59][60][61][62][63][64]. Many studies reported that antioxidant compounds also have antimutagenic, anti-genotoxic and anti-cancerogenic effects [7,65,66]. This fact challenged us to study the anti-cytotoxic and anti-genotoxic potential of rose hydrosols against the direct mutagen MNNG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have well-expressed pharmacological and antioxidant activities [50,[58][59][60][61][62][63][64]. Many studies reported that antioxidant compounds also have antimutagenic, anti-genotoxic and anti-cancerogenic effects [7,65,66]. This fact challenged us to study the anti-cytotoxic and anti-genotoxic potential of rose hydrosols against the direct mutagen MNNG.…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing interest in various plant products and compounds of plant origin that help cells to activate their defence mechanisms. Essential oils [1][2][3][4] and hydrosols and extracts [5][6][7][8] of oleaginous plants have many biological effects due to the wide range of compounds they contain. These compounds contribute to their healing effects, including the protection of the genome against injuries caused by factors of different origin.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC reference standards, rosmarinic acid (99%), and luteolin 7- O -glucoside (98.9%), were purchased from Phytolab (Vestenbergsgreuth, Germany). All the chemical reagents used for the CBMN assay are reported in our previous work [ 58 ] (see Supplementary Materials Section S3.1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The statistical analysis was conducted according to previous work [ 58 ] (see Supplementary Materials Section S3.7.3 ).…”
Section: Methodsmentioning
confidence: 99%
“…This presents a challenge to investigate the mechanisms of action, bioavailability, pharmacokinetics, active ingredients, and industrialization of products in the metabolites of potentially medicinal plants to add curative, preventative, and innovative effects against various mild and/or chronic diseases (Rojas et al, 2003;Gordillo et al, 2019). One of them is the species Equisetum arvense, commonly called "horsetail," a widely used for its antioxidant, antimicrobial, anti-inflammatory, antidiabetic, and other benefits (Al-Snafi, 2017), as well as its cytotoxic and antigenotoxic effects by activating antioxidant transcription in the promoter regions of genes that induce oxidative stress, limiting cancerous proliferation (Batir-Marin et al, 2021;Dormousoglou et al, 2022), with diuretic, antiprostatic, and renal properties thanks to flavonoids and potassium salts, which also confer demineralizing properties and contribute to the maintenance of collagen by increasing tissue elasticity (Batir-Marin et al, 2021;Boeing et al, 2021). Desmodium molliculum also known as "dog's paw" or "Manayupa," is an intriguing plant with multifunctional properties very similar to those of E. arvense, as demonstrated by studies demonstrating its high healing capacity, antiasthmatic, anti-inflammatory, antibacterial, contraceptive, antioxidant, and hepatoprotective, effects, associated with alleviating fevers, relieving inflammation, and other diseases (Boeing et al, 2021), associated with alleviating fevers, dysentery, liver diseases, wound healing, ulcers, eye diseases, abdominal tumors, asthma, nasal polyps, menstrual disorders, colds, and kidney problems, among many others (Ayala-Mata et al, 2020;Olascuaga-Castillo et al, 2020;Joshi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%